Revitalisasi Seni Budaya Wayang melalui Tayangan Televisi - Agus Maladi Irianto (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2018)
AbstractThe development of traditional art is the development of artistic values and art appreciation in order to increase the artist and community's friendship. Ideally the arts as part of the national culture derive its meaning in terms of understanding and appreciation of cultural values. Therefore, to improve the resilience of the nation's culture, then the national development needs to be dotted from the efforts of art development that can give birth to